Dinucleotide microsatellite markers in the genus Caulerpa - E, Varela-Álvarez (2014)
Caulerpa spp. are clonal green marine algae which often act as invasive species when growing outside their native biogeographical borders. Over the two past decades, Caulerpa taxifolia has spread along the Mediterranean coast, presently occurring at 70 sites and covering nearly 3,000 ha of subtidal area. New genetic markers (microsatellites) have been developed to assess clonal structure and genetic diversity of recently established populations of the invasive species C. taxifolia and Caulerpa racemosa in comparison with populations of the native Caulerpa prolifera in the Mediterranean. Our results show that nine polymorphic markers have been developed for C. prolifera, seven for C. taxifolia, and three for C. racemosa. Genetic diversity in Caulerpa was assessed in two geographical scales: one at a population scale where 40 thalli units were collected from C. prolifera in Cala d’Or, Mallorca, Spain, and another at a species scale, where 30 sample units were analyzed for C. prolifera, 24 for C. taxifolia, and 24 for C. racemosa from different sites in the Mediterranean, Atlantic, and Pacific Ocean. Number of alleles, expected heterozygosity, and marker amplification success are provided in each case.